Committee on Economic Education (American Economic Review, 2014)
The committee held the third Conference on Teaching and Research in Economic Education (CTREE) at the Renaissance Hotel in Chicago, IL, May 29–31, 2013. The program committee of Tisha Emerson (Chair), KimMarie McGoldrick, and Steven Cobb performed substantial work and put together an exemplary program. The third conference continued successes of the first two CTREE conferences. Four plenary speakers addressed the conference: Derek Neal (Chicago), John List (Chicago), Spencer Krane (Federal Reserve Bank of Chicago), and Justin Wolfers (Michigan). The conference also held a special morning presentation by Myles Boylan of the National Science Foundation. The title of the presentation was “NSF Funding Opportunities for Economic Education Research and Improvement.” The special NSF and plenary sessions were all well attended and received. The Chicago Federal Reserve hosted a dinner and a plenary talk from Spencer Krane of the Chicago Federal Reserve Bank. The Chicago Fed also provided a tour of their money museum to interested conference attendees. Cindy IvanacLillig and other staff of the Chicago Fed provided their time and resources to make this possible. Gail Hoyt worked with AEA staff to coordinate the presence of publishers at the conference. In addition to plenary sessions, 64 papers were presented at 21 sessions, and 5 panel discussions and 2 “how-to-do-it” workshops were offered. Registration for the conference was 290, about a 12 percent increase from the year before. The fourth conference will be May 28–30, 2014 at the Washington, DC, Marriott at Metro Center. The conference will feature plenary talks from Cecilia Rouse (Princeton), Alan Blinder (Princeton), and Ken Elzinga (Virginia). The Board of Governors of the Federal Reserve has committed to providing a speaker, but the speaker has not yet been identified. The Journal of Economic Education remains a co-sponsor of the conference. Those presenting papers were again given the opportunity to submit their papers from the conference for possible Committee on Economic Education